Entwicklung und Evaluierung einer tanzbasierten Bewegungstherapie für Patienten mit Hämophilie - Czepa, D.; van Ravenstein, S.; Stäuber, F.; Hilberg, T. (Hämostaseologie, 2013)
So far, the use of methods derived from creative arts has not been considered in the haemophilia treatment. The aim was to investigate the expectations for a dance-based exercise therapy for patients with haemophilia and the extent of its acceptance. Patients, method: The one-hour dance-based exercise therapy was offered to 30 haemophilia patients (HI30) (49 ± 11, 30–67 years). For the evaluation of expectations, questionnaires were created and filled out by participants before and after the intervention. Additionally, 19 haemophilia patients (HF) and 20 controls without haemophilia (KF) who did not participate in the intervention were also questioned. The results show that haemophilia patients have more experience in dance than controls (HI30:62%, HF:74%, KF:45%). In contrast, the proportion of those who are currently dancing is higher in controls without haemophilia (HI30: 17%, HF: 10%, KF: 26%). The termination of dance activity in patients with haemophilia who were part of the intervention was mainly due to pain (HI30: 40%, HF: 29%, KF: 0%), whereby controls without intervention terminated the dance activity mainly due to lack of time (HI30: 30%, HF: 57%, KF: 56%). Ultimately, 24 out of 30 patients with haemophilia (HI24) completed the intervention. All HI24 met their expectations. 38% felt limited by haemophilia while carrying out the exercises. The majority of the participants were able to follow the exercises well (96%) and were did not overstrain physically (92%) nor mentally (87%), also 79% did not have pain. 23 of HI24 (96%) can envision a continuation of the dance-based exercise therapy. Conclusion: The experience with the dance-based exercise therapy was predominantly positive. It represents an alternative sports therapy programme for patients with haemophilia. Further studies are needed in order to make statements concerning the long-term use of such training.
Keywords: Haemophilia; dance-based exercise therapy; expectations; pain